Formation and characterization of soy protein nanoparticles by controlled partial enzymatic hydrolysis. (August 2020) - Shen, Penghui; Zhou, Feibai; Zhang, Yuanhong; Yuan, Dan; Zhao, Qiangzhong; Zhao, Mouming
Abstract: In the present study, the potential of enzymatic hydrolysis as an efficient approach for the fabrication of soy protein nanoparticles (SPNPs) was investigated. Three types of enzymes including Flavorzyme, Alcalase and Protamex were selected to hydrolyze soy protein isolate (SPI) to different degrees (DH, 3%, 7% and 11%). Both the enzymes used and the DH obtained were vital for nanoparticle formation. The fabricated SPNPs were spherical and showed homogeneous size distributions with z-average size between 80 and 170 nm. Mechanisms involved in the formation of SPNPs were discussed by evaluating changes in SDS-PAGE patterns, secondary structures and interactive forces maintaining particle structure. Results suggested that the main subunits of 7S and 11S were retained in SPNPs, where hydrophobic interactions mainly dominated their structure formation, along with hydrogen bonds and disulfide bonds stabilizing the external and internal structure of nanoparticles, respectively. Secondary structure analysis implied that the ratio of α -helix to β -sheet in SPNPs was in a narrow range of around 45%, and a transition from α -helix to β -sheet was impeditive for nanoparticle formation. Compared with native SPI, the SPNPs showed more rapid adsorptions toward the oil-water interface, suggesting the potential good emulsifying property. Meanwhile, enhanced surface hydrophobicity and hydrolysis of α′α subunits into polypeptides endowed SPNPs with superior antioxidative capacity. These findings are expected to expand the potential of partial enzymatic hydrolysis as an efficient strategy to design and construct multifunctional soy protein nanoparticles for foods, cosmetics, and pharmaceutical applications. Graphical abstract: Image 1 Highlights: Soy protein nanoparticles (SPNPs) were fabricated by controlled partial enzymatic hydrolysis. SPNPs were spherical and uniformly distributed with mean particle size between 80–170 nm. SPNPs were dominantly maintained by hydrophobic interactions, disulfide bonds and hydrogen bonds. The ratio of α -helix to β -sheet in SPNPs was in a narrow range of around 45%. SPNPs showed favorable anti-oxidative activity.